Poczucie odmienności i osamotnienia u dzieci zdolnych = The feeling of otherness and loneliness of gifted children - Pufal-Struzik, Irena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses the problem of loneliness of some gifted children. It is caused by their unique individual characteristics, e.g. their high level of intellect, a strong sensitivity and intensity of living, unique look at the phenomena of the surrounding world, a deep self-awareness (self-reflection and insight into each other), a wider range of knowledge, different than their peers? ways of thinkingand many other features.
Keywords: dzieci zdolne; cechy indywidualne; poczucie samotności; gifted children; individual qualities; a sense of loneliness